2022
DOI: 10.1002/cjoc.202200200
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Doped 10H‐Phase Perovskite BaCo0.8Fe0.15Ir0.05O3δ as an Efficient Oxygen Evolution Reaction Catalyst

Abstract: Comprehensive Summary Designing low‐cost and high‐performance catalysts of electrocatalytic oxygen evolution reaction (OER) has always been one of the hot topics in current research. Hexagonal perovskite materials show great application potential in this field. Here, we synthesized 5% Iridium (Ir)‐doped hexagonal phase perovskite BaCo0.8Fe0.15Ir0.05O3–δ (BCFI). Using the Rietveld method to refine the structure, combining with the spherical aberration corrected high‐angle annular dark‐field scanning transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…[ 32 ] Beside the satellite peak at 715.5 and 725.1 eV, the peaks at 712.4 and 723.0 eV belong to Fe 3+ . [ 19,35 ] The splitted peaks unveal the existence of Fe oxide and hydroxide. As shown in Figure 4g, the peaks at 777.8 and 795.8 eV correspond to the 2p 3/2 and 2p 1/2 peaks of metallic Co. [ 36‐37 ] In addition, the peaks at 780.5 and 796.4 eV along with 783.3 and 798.0 eV can be ascribed to the 2p 3/2 and 2p 1/2 peaks for the Co 3+ and Co 2+ , respectively, [ 38 ] indicating the coexistence of metallic Co and high‐valence Co.…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 ] Beside the satellite peak at 715.5 and 725.1 eV, the peaks at 712.4 and 723.0 eV belong to Fe 3+ . [ 19,35 ] The splitted peaks unveal the existence of Fe oxide and hydroxide. As shown in Figure 4g, the peaks at 777.8 and 795.8 eV correspond to the 2p 3/2 and 2p 1/2 peaks of metallic Co. [ 36‐37 ] In addition, the peaks at 780.5 and 796.4 eV along with 783.3 and 798.0 eV can be ascribed to the 2p 3/2 and 2p 1/2 peaks for the Co 3+ and Co 2+ , respectively, [ 38 ] indicating the coexistence of metallic Co and high‐valence Co.…”
Section: Resultsmentioning
confidence: 99%
“…In Ir 4f spectra (Figure 1f), the two peaks located at 61.2 and 64.0 eV are assigned to the Ir 4f 7/2 and Ir 4f 5/2 peaks of metallic Ir. 50,51 Besides, the strong shoulder peaks at 62.3 and 65.2 eV are attributed to the Ir−O species, 52 which may be caused by the strong metal support interaction or oxidation of Ir surface. 53 As shown in Figure 1g, it can be concluded that Co 2+ and Ni 2+ species exist in all of the samples because of the CoNiP 4 O 12 support.…”
Section: Characterizations Of Mpmentioning
confidence: 99%
“…It is worth noticing that the optimized electronic and structural electrocatalysts are required to overcome the energy barrier of water dissociation and accelerate OH ad transfer in alkaline water splitting. [ 16‐19 ] MoNi 4 ‐based electrocatalyst is a promising candidate for HER and OER due to their easily tuned electronic structure and high conductivity. [ 20‐21 ] Furthermore, various strategies (such as morphology engineering, defect engineering, heterostructure engineering, etc .)…”
Section: Background and Originality Contentmentioning
confidence: 99%